Five Factors in Social Network Site Advertisement Influencing the Purchase Intention of Generation Z - Atmawijaya, Melissa Adira Puteri; Bangsawan, Satria; Ramelan, Mudji Rachmat (PT FORMOSA CENDEKIA GLOBAL, 2024)
In the realm of digital marketing, understanding the factors that influence Online Purchase Intention is imperative for the success of advertising campaigns. This research investigates the specific elements shaping consumer intentions within the context of Skintific Advertisement on Instagram. This study focuses on the effect of the of five factors in SNS advertisement, namely; information, entertainment, trust, disturbance, and social interaction, on online purchase intention. The research was conducted on Skintific Instagram followers who have made purchases on Skintific products. This research was conducted quantitatively on 151 respondents. The method used is Structural Equation Model with SmartPLS 3.3.3 software in 2024. Statistical results after hypothesis testing show thathypotheses one, two, three, four five, and six are proven, and it can be concluded that information, entertainment, trust, disturbance, and social interaction all have a positive and significant effect on online purchase intention.